If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(2 + -1x) = 25x (2 * 12 + -1x * 12) = 25x (24 + -12x) = 25x Solving 24 + -12x = 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 24 + -12x + -25x = 25x + -25x Combine like terms: -12x + -25x = -37x 24 + -37x = 25x + -25x Combine like terms: 25x + -25x = 0 24 + -37x = 0 Add '-24' to each side of the equation. 24 + -24 + -37x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -37x = 0 + -24 -37x = 0 + -24 Combine like terms: 0 + -24 = -24 -37x = -24 Divide each side by '-37'. x = 0.6486486486 Simplifying x = 0.6486486486
| -16.9x=-84.5 | | 6.3x=-88.2 | | 3.9=11.31 | | 16v+7=15v+1 | | 5(m+3)= | | -n^2+2n+17=0 | | .15s-6=9s+9 | | 9x+3=15+3x | | 6x^2-17xy-3y^2+22x+10y-8=0 | | 5x-3=12x+3 | | 8x+9=-7 | | 250+0.25x=x | | 5x^4=6x^2+2 | | 2x^2-xy+5x-2y+2=0 | | 6x-40=x-36 | | 3x-20=x-18 | | 4x+x+7=44 | | 8x+48=2x+90 | | 6x-30=50-4x | | 6x-1=104-9x | | 11x+6=2x+87 | | -5=2x+13 | | 12=7x+-4 | | 4m+2=-3m+16 | | 4x-5=103-8x | | 5(x-3)+12= | | 6x-30=42-6x | | 5m-21-3m+38=-5 | | 4+8(x-2)=4 | | m-5-4m=-18 | | 2x+3.2=0 | | y(y+14)=48 |